The associations between identity and both risk and protective factors related to violent recidivism in adult forensic psychiatric patients - Tressová, Deni (Crime & delinquency, 2025)
This study investigated identity (i.e., clinical identity, identity dimensions, and identity styles) and its associations with violent recidivism in forensic psychiatric patients. Using surveys and patient records, correlational analyses showed that all three identity approaches were associated with risk and protective factors linked to violent recidivism. Moreover, regression analyses showed that various identity constructs were associated with reduced self-reliance and higher violation of terms and agreements (disturbed identity and lack of identity), the risk scale (exploration in breadth), and lower impulsivity (information-oriented style). The findings suggest to incorporate identity assessment during the diagnostic phase as well as during treatment, as developing a healthy identity could act as an entrance for the treatment of risk factors and strengthening of protective factors.